Review of Islamic Law Regarding Elephant Ivory as a Wedding Dowry in Flores NTT Customs - Ahmad Saputra; Muhammad Bintang; Nur Hasan (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This study aims to determine the views of the Lamoholot community in waowala village, ile Ape sub-district, Lembata Regency NTT on belis in the marriage tradition. belis is a tradition that has noble values and a form of respect for women. as for the purpose of belis, namely a tool to determine the legality of a marriage, as a marker that the girl has left her legal family, and as a tool to raise the name / degree of the male family. In East Nusa Tenggara there are various belis used in the form of gold, silver, money, or animals such as cows, or horses. elephant ivory is difficult to obtain. although elephant ivory is very difficult to obtain, this tradition still applies and is maintained by the Lameholot community. In the Islamic review, the use of elephant ivory as a wedding dowry in the East Flores custom has a high value and is very suitable to be used as a dowry, and does not conflict with Islamic teachings.